2019
DOI: 10.1177/1479164119845904
|View full text |Cite
|
Sign up to set email alerts
|

Association of central arterial stiffness with the presence and severity of diabetic retinopathy in Asians with type 2 diabetes

Abstract: PurposeOsteopontin (OPN) is a proinflammatory cytokine with diverse functions. Increased levels of OPN in vitreous fluid have been reported in patients with diabetic retinopathy (DR); however, studies on circulating OPN levels in DR are limited. We aim to examine the association of plasma OPN levels with the presence and severity of DR in a multiethnic cohort with type 2 diabetes mellitus (type 2 diabetes) in Singapore.MethodsPlasma levels of OPN were measured using enzyme-linked immunosorbent assay. Digital c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(38 citation statements)
references
References 62 publications
3
35
0
Order By: Relevance
“…Finally, it has been previously shown that patients with proliferative diabetic retinopathy featured significantly greater PWV compared to those having either background diabetic retinopathy or a normal fundoscopy, after adjustment for other risk factors . In a more recent study, it was demonstrated that arterial stiffness evolves as a determinant of the presence and severity of diabetic retinopathy among patients with T2DM, increasing the odds for both non‐proliferative (OR: 1.10, 95% CI 1.03‐1.17) and proliferative diabetic retinopathy (OR: 1.15, 95% CI 1.06‐1.25) …”
Section: Arterial Stiffness and Microvascular Complicationsmentioning
confidence: 93%
“…Finally, it has been previously shown that patients with proliferative diabetic retinopathy featured significantly greater PWV compared to those having either background diabetic retinopathy or a normal fundoscopy, after adjustment for other risk factors . In a more recent study, it was demonstrated that arterial stiffness evolves as a determinant of the presence and severity of diabetic retinopathy among patients with T2DM, increasing the odds for both non‐proliferative (OR: 1.10, 95% CI 1.03‐1.17) and proliferative diabetic retinopathy (OR: 1.15, 95% CI 1.06‐1.25) …”
Section: Arterial Stiffness and Microvascular Complicationsmentioning
confidence: 93%
“…As a consequence, the outer retinal layers may be more exposed, and damaged by increased flow pulsatility related to increased large artery stiffness, although this hypothesis needs to be confirmed. Large artery stiffness has been shown to be related to diabetic retinopathy (58), age-related macular degeneration (59) and retinal microvascular impairment (60, 61). Exaggerated pulsed retinal capillary flow, in contrast to unchanged mean retinal capillary flow, and stiffer wall properties of retinal arterioles has been observed in patients with treated resistant hypertension compared with patients with grade 1–2 hypertension (62).…”
Section: Clinical Relevance Of the Pulsatile Interaction Between The mentioning
confidence: 99%
“…A significant association between carotid disease and changes in the retinal microvasculature has also been found in adolescents with T1D [38]. Diabetic retinopathy has also been associated with other markers of peripheral arterial disease [39], peripheral vascular disease in T1D [40], and arterial stiffness [41].…”
Section: Discussionmentioning
confidence: 96%